The influence of embedded generator control modes on an electrical distribution network power flows and voltage profile - Azizan A.W.; Ramachandaramurthy V.K.; Loo C.K. (2023)
When an individual synchronous generator is remotely connected to an electrical power distribution network, the power it generates influences power flows in and out of the interconnection bus point so that the bus voltage profile varies. Voltage profile varies as the embedded generator's power reduces or increases. This variation will be illustrated by the embedded power generation modes, namely the PQ and PV modes. This paper intends to explore the effects an embedded generation modes have on an electrical power distribution system's power flows and its voltage profile by using PSCAD/EMTDC power simulation software on a selected Malaysian distribution network. The simulation result shows the embedded generation in PQ mode causing distinctive oscillation thus resulting in network voltage fluctuation. 2009 IEEE.